Microbiological analysis of pasteurized and fresh fruit juice sold in Rawalpindi of Pakistan (Bangladesh Journal of Scientific and Industrial Research, 2013)
Freshly prepared and pasteurized fruit juices sold by vendors in local market of Rawalpindi city from 10 locations were analyzed for the microbiological quality. Total viable count (TVC), total coliform, faecal coliform, molds and the presence of pathogenic microorganisms such as E. coli, Pseudomonas, Staphylococcus aureus, Salmonella, and fungi like Aspergillus, Pencillum, Rhizopus were determined .In open fruit juices available in city were highly contaminated with bacteria and fungi. E. coli, Salmonella, Staphylococcus, and Pseudomonas were isolated with different frequency. Aspergillus, Pencillum and Rhizopus were also found in juices especially Aspergillus was with high percentages. The pasteurized juices have less contamination as compared to the fresh juices samples. The number and type of microorganisms recovered from the freshly squeezed fruit juices made them unsafe for drinking. The results of this study demonstrate the unhygienic quality of popular types of market vended freshly squeezed fruit juices and their risk to the consumers. DOI: http://dx.doi.org/10.3329/bjsir.v48i3.17329 Bangladesh J. Sci. Ind. Res. 48(3), 185-192, 2013